2021
DOI: 10.2991/efood.k.210318.001
|View full text |Cite
|
Sign up to set email alerts
|

Food‐derived Acetylcholinesterase Inhibitors as Potential Agents against Alzheimer’s Disease

Abstract: Acetylcholinesterase (AChE) is a critical enzyme involved in nerve functions and signal transmission within the brain. However, during aging, excessive AChE activity often leads to rapid and progressive depletion of acetylcholine (ACh), the major neurotransmitter. Shortage of ACh leads to reduced neurotransmission and the development of pathological conditions such as dementia and Alzheimer's Disease (AD). Therefore, one of the proven approaches toward the clinical management of AD is the use of compounds that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 56 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…BAPs can be produced from edible seeds through enzymatic hydrolysis of the protein using proteinases such as thermolysin, savinase, flavourzyme, elastase, trypsin, pepsin, chymotrypsin, alcalase, and pancreatin alone or in various combinations [33][34][35][36][37]. Hydrolysates of food proteins are frequently achieved via digestion (enzymatic) followed by subsequent separation of the peptides (soluble phase) from undigested proteins (insoluble phase) [38]. Protein hydrolysis is commonly regulated by the release of H + (proton) that builds up and reduces the pH of the mixture as the enzymatic reaction progresses with time.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…BAPs can be produced from edible seeds through enzymatic hydrolysis of the protein using proteinases such as thermolysin, savinase, flavourzyme, elastase, trypsin, pepsin, chymotrypsin, alcalase, and pancreatin alone or in various combinations [33][34][35][36][37]. Hydrolysates of food proteins are frequently achieved via digestion (enzymatic) followed by subsequent separation of the peptides (soluble phase) from undigested proteins (insoluble phase) [38]. Protein hydrolysis is commonly regulated by the release of H + (proton) that builds up and reduces the pH of the mixture as the enzymatic reaction progresses with time.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…Most drugs, such as levodopa, ropinirole (dopaminergic), used in the treatment of Parkinson's disease and other motor disorders (Lee 2019); donepezil, galantamine (cholinesterase inhibitors), used in the treatment of cognitive disorders (Hogan et al 2008); and antipsychotic drugs (chlorpromazine, haloperidol, aripiprazole, and benzodiazepines), used for the management of behavioral and psychological disorders (Tifratene et al 2017) are symptomatic (Chen and Pan 2015). These drugs have been associated with several undesirable side effects, including decreased heart rate, decreased appetite, and loss of weight (Aluko 2021). Hence, the direction has been shifted toward the use of some foods with acclaimed anti-neurodegenerative properties to prevent and manage these geriatric brain aging conditions.…”
Section: Anxiety Depression and Brain Agingmentioning
confidence: 99%
“…The therapeutic use of piperine restores monoamine neurotransmission, thus alleviate cognitive impairment and slow the progression of Alzheimer's disease (Wang et al 2019). Piperine can attenuate the increase in lipid peroxidation and AChE activity (Mirmosayyeb et al 2017) and has been shown to reduce brain levels of AChE, which is connected to improvements in memory functions (Aluko 2021). It also exerts an anti-inflammatory effect in attenuating cerebral ischemic damage by modulating nuclear factor-kappa β (NF-κβ) (Vaibhav et al 2012).…”
Section: Piper Guineense Role In Managing Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations